Fenomenologicko-pragmatistická interpretace hyperkonektivistického světa: k problémům filosofie informace - Černý, Michal (Masaryk University Press, 2020)
Title in English: Phenomenological-pragmatist interpretation of the hyper-connectivist world: on topics of philosophy of information Against the background of the ideas of selected phenomenologists (Martin Heidegger, Jan Patočka, Jan Sokol) and pragmatist philosophers (Marc Johnson, Georg Lakoff or Antonio Damasio), the monograph reflects the phenomenon of the philosophy of information in a new framework than Luciano Floridi does. The monograph takes much more on transforming the contemporary world and its relationship to education and thought. On the example of individual sub-facets, they form a comprehensive critical reflection on how it is possible with the philosophy of information and the philosophy of education. It strives to be a clear guide to the contemporary world, which is trying to think new ways.